RETRACTED: On the theoretical study of the phenomena of electromagnetism with variable core parameters - Yusupova Anora; Aliyev Ibratjon; Kholmatov Erkinjon; Abduraxmonov Sultonali (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001